3D Printing of Liquid Crystal Elastomeric Actuators with Spatially Programed Nematic Order. Issue 10 (15th January 2018) - Kotikian, Arda; Truby, Ryan L.; Boley, John William; White, Timothy J.; Lewis, Jennifer A.
Abstract: Liquid crystal elastomers (LCEs) are soft materials capable of large, reversible shape changes, which may find potential application as artificial muscles, soft robots, and dynamic functional architectures. Here, the design and additive manufacturing of LCE actuators (LCEAs) with spatially programed nematic order that exhibit large, reversible, and repeatable contraction with high specific work capacity are reported. First, a photopolymerizable, solvent‐free, main‐chain LCE ink is created via aza‐Michael addition with the appropriate viscoelastic properties for 3D printing. Next, high operating temperature direct ink writing of LCE inks is used to align their mesogen domains along the direction of the print path. To demonstrate the power of this additive manufacturing approach, shape‐morphing LCEA architectures are fabricated, which undergo reversible planar‐to‐3D and 3D‐to‐3D′ transformations on demand, that can lift significantly more weight than other LCEAs reported to date. Abstract : 3D liquid‐crystal elastomer actuators with programed director alignment are designed and fabricated via highoperating‐temperature direct ink writing. The additive manufacturing method produces dynamic shape‐morphing architectures in arbitrary form factors that are capable of lifting heavy loads.